Dual strategy testing with electrochemiluminescence and ELISA for sero-prevalence of transfusion transmitted viral infections in blood bank - Dr. Ravikanti; Dr. Siddaganga S.M.; Dr. Sunitha. B.R.; Dr. G. Vishwanath; Dr. Jagadeshwari K. (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Transfusion transmittable infections (TTI) continue to be a major threat to safe transfusion practices. Blood is one of the major sources of transmission of infectious diseases viz. human immunodeficiency virus (HIV), hepatitis B virus (HBV), hepatitis C virus (HCV), syphilis, malaria, and many other infections in India. Screening assays for the infectious diseases with excellent sensitivity and specificity helps to enhance the safety of the blood transfusions reducing the diagnostic window period as much as possible. Methods: The present study was designed to determine the seroprevalence of Transfusion Transmittable Infections viz., HIV, HCV, and HBV, Syphilis, malaria among the blood donors in blood bank from January 2013-December 2013. In the present study Sera samples were screened for hepatitis B surface antigen (HBsAg), antibodies to HCV, HIV using electrochemiluminescence and to syphilis using Rapid Plasma Reagin test (RPR), and to malaria by peripheral smear respectively. All samples were screened for HIV, HBsAg, HCV, syphilis and malaria. Results: Total 9,400 cases. Of which 51% were voluntary donors and 49% were replacement donors. The overall prevalence of HIV, HbsAg, and HCV were 0.35,1.86, and 0.22 respectively. All the markers tested there was increased prevalence of TTI among the replacement donors as compared to voluntary donors. 2.4% donors had infection of each HIV, HbsAg, and HCV. 0.21% donors had infection of both HIV and HCV. Conclusion: The screening of blood and blood components by dual testing strategy using high sensitivity serological assay like enhanced chemiluminescence technology and NAT helps in detecting the potentially infectious blood units in all phases of infection, which aids in enhancing the safety of blood transfusion and reducing the potential risk of post-transfusion infection.